Assessing the performance of multiple drug supply chain management in Odisha health services using LSAT score and stock-out situation - Sambit Kumar Behera; Srinivasan Kannan (Cogent Business & Management, 2018)
Purpose of the article is to assess the performance of Odisha's health services' multiple drug supply chain management using logistics system assessment tool (LSAT) and logistics indicators assessment tool (LIAT). Data were collected on public health supply chains at different levels, state, district, sub-district, or block. For that purpose 13 block level institutions from two districts of Odisha were included. Drug and logistics supply chains of essential drugs, and national programmes were studied. Poorly coordinated Supply chain lead to stock-out of more than 15% of total number of products was higher in backward districts and rural areas. The mean for number of days of stock-out per product were found to be highest at the block level. When we looked for Logistic management unit they were present only at the state head quarters for specific national programmes.
Keywords: 650